Validity of Learning Package for Environmental Change Materials in Implementing Student Worksheets Based on Contextual Teaching and Learning (CTL) - Intan Dwi Puspitasari; Herlina Fitrihidajati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2022)
This study aims to produce learning package in the form of lesson plans and valid questions in implementing student worksheets based on Contextual Teaching and Learning (CTL) which is to complement learning package other than student worksheets in previous research. This research method uses a 4-D development model which the disseminate stage is not done, namely define, design, and develop. The research target is learning package such as lesson plans and questions. Place and time of study in September 2021 at Biology Department of Universitas Negeri Surabaya. The research parameter measured was the validity of the learning package by taking into account several aspects. The validity of the lesson plans includes aspects of syllabus identity, syllabus conformity with lesson plans, lesson plans identity, formulating indicators, formulating learning objectives, learning materials, learning methods, learning tools and resources, learning activities and outcome assessment study. Aspects of question validity include material feasibility, construction feasibility, grammatical aspects, and character aspects of measuring scientific literacy. Based on the data above, the validation of the questions obtained an average score of 90% with a very valid category and the lesson plan validation is an average score of 92.96% with a very valid category. The conclusion of this study shows that the test of the validity of the learning package in the form of lesson plans and questions obtained a score above 70%. This shows that the learning level is valid. Keywords: Validity, Scientific Literacy, Environmental Change, Learning Package.